The Role of DPMD in Encouraging Village Economic Empowerment Programs in Ciamis Regency - febriani, fika; Ikhtia Faizatuz Zahrah; Ida Noviyanti; Dio Alip Fadilla; Paisal Topan Nugraha; Regi Refian Garis (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
The purpose of this study is to see the role of DPMD in encouraging village economic empowerment programs in Ciamis Regency. Empowerment has an important role in good governance to increase independence in the community This research uses a qualitative approach to describe the problem and the focus of the research. The results of this study show that DPMD's strategic role in supporting village economic empowerment programs includes policy formulation and regulation, guidance and facilitation, monitoring and evaluation, and collaboration and coordination. There are also positive impacts of DPMD's role in village economic empowerment, including Increasing Village Original Income (PAD), Developing Village Business, and Increasing Human Resource Capacity. BUMDes have great potential to improve the welfare of rural communities. DPMD has an important role in supporting and developing BUMDes in order to achieve their maximum potential.